Encapsulation of Pomegranate Peel Extract (Punica Granatum L.) by Double Emulsions: Effect of the Encapsulation Method and Oil Phase - Gimenez-Castillo, B (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Pomegranate peel is an agro-industrial waste that can be used as source of punicalagin, a polyphenolic compound with several beneficial effects on health. Since, once extracted, punicalagin is prone to degradation, its encapsulation by double emulsions can be an alternative to protect the active compound and control its release. The aim of this investigation was to evaluate the feasibility of encapsulating pomegranate peel extract (PPE) in double emulsions using different types of oils (castor, soybean, sunflower, Miglyol and orange) in a ratio of 70:30 (oil:PPE) and emulsification methods (direct membrane emulsification and mechanical agitation), using polyglycerol polyricinoleate (PGPR) and Tween 80 as lipophilic and hydrophilic emulsifiers, respectively. Direct membrane emulsification (DME) led to more stable emulsions during storage. Droplet size, span values, morphology and encapsulation efficiency (EE) were better for double emulsions (DEs) prepared by DME than for mechanical agitation (MA). DEs formulated using Miglyol or sunflower oil as the oily phase could be considered as suitable food grade systems to encapsulate punicalagin with concentrations up to 11,000 mg/L of PPE. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.